Blood lead level risk factors and reference value derivation in a cross-sectional study of potentially lead-exposed workers in Iran - Sareh Nakhaee; Alireza Amirabadizadeh; Samaneh Nakhaee; Mahmood Zardast; Jonathan Schimmel; Jalil Ahmadian-Moghadam; Ayob Akbari; Homeira Mohammadian Darmian; Maryam Mohammadi; Omid Mehrpour (BMJ Open)
Objectives This exploratory investigation aimed to measure blood lead levels and associated risk factors in exposed workers in Iran, and to derive appropriate reference values for blood lead in this population as a means of epidemiological comparison.Design Cross-sectional.Setting Manufacturing plants with potential lead exposure in Southern Khorasan Province, Iran.Participants The study included 630 workers, selected through stratified random sampling.Primary and secondary outcome measures The primary measures in this exploratory investigation were venous blood lead concentration (BLC) and associated risk factors of age, gender, work experience, cigarette smoking and history of opium use. The secondary measures were symptoms associated with lead toxicity. Data analyses were conducted using Student’s t-test, Mann-Whitney U test, one-way analysis of variance, Kruskal-Wallis test, Spearman correlation coefficient and regression analysis.Results Mean and median BLCs were 6.5±8.1 μg/dL and 3.9 μg/dL (IQR: 2.9–5.8), respectively. Of the subjects, 85 (13.5%) had BLC ≥10 μg/dL. The derived reference BLC value in this study was 30 μg/dL for men and 14 μg/dL for women. Increasing work experience and age were associated with BLC >10 μg/dL. Radiator manufacturers were up to 12.9 times (95% CI 4.6 to 35, p<0.005) more likely than painters to have BLC >10 μg/dL. Most subjects reported multiple symptoms.Conclusions The mean BLC was above the maximum recommended concentration. There was a significant relationship between higher BLC and age or working in a printing factory or radiator manufacturing. These findings can direct efforts towards reducing occupational lead exposure.